The Interplay of Recent Vegetation and Sea Ice Dynamics—Results From a Regional Earth System Model Over the Arctic. Issue 6 (16th March 2020) - Zhang, W.; Döscher, R.; Koenigk, T.; Miller, P.A.; Jansson, C.; Samuelsson, P.; Wu, M.; Smith, B.
Abstract: Recent accelerated warming over the Arctic coincides with sea ice reduction and shifting patterns of land cover. We use a state‐of‐the‐art regional Earth system model, RCAO‐GUESS, which comprises a dynamic vegetation model (LPJ‐GUESS), a regional atmosphere model (RCA), and an ocean sea ice model (RCO), to explore the dynamic coupling between vegetation and sea ice during 1989–2011. Our results show that RCAO‐GUESS captures recent trends in observed sea ice concentration and extent, with the inclusion of vegetation dynamics resulting in larger, more realistic variations in summer and autumn than the model that does not account for vegetation dynamics. Vegetation feedbacks induce concomitant changes in downwelling longwave radiation, near‐surface temperature, mean sea level pressure, and sea ice reductions, suggesting a feedback chain linking vegetation change to sea ice dynamics. This study highlights the importance of including interactive vegetation dynamics in modeling the Arctic climate system, particularly when predicting sea ice dynamics. Plain Language Summary: Recent accelerated warming over the Arctic is associated with dramatic changes in the physical environment, among which unprecedented sea ice decline has received particular attention. In this study, we use a regional Earth system model accounting for interactive coupling between the atmosphere, land vegetation, and sea ice dynamics to explore their potential links. Our model simulates observed spatiotemporal patterns of sea ice thickness and extent reasonably well. Furthermore, the results show that feedbacks of warming‐driven vegetation changes on the near‐surface radiation balance can cause greater variations in sea ice between seasons, which can contribute to an accelerated trend of sea ice reduction. The changes in mean sea level pressure caused by vegetation changes can alter the transport of energy and warm the land, sea, and sea ice surfaces. Downwelling longwave radiation is the dominant factor contributing to the near‐surface warming and increased sea ice melting. Our study highlights the importance of adopting fully coupled Earth system models that account for interactive effects of vegetation dynamics on the physical climate system, in particular when analyzing the reduction of sea ice in the Arctic. Key Points: Sea ice concentration and extent are simulated by a fully coupled regional Earth system model, including interactive vegetation dynamics Interactive vegetation dynamics increase the interannual variations of seasonal sea ice cover Increased downwelling longwave radiation induced by vegetation feedbacks enhances sea ice melting